Bakteri Asam Laktat Lactobacillus Plantarum C410LI dan Lactobacillus Rossiae LS6 yang Diisolasi dari Lemea Rejang terhadap Suhu, pH dan Garam Empedu Berpotensi sebagai Prebiotik - Yenni Okfrianti; Darwis Darwis; Ayu Pravita (Poltekkes Kemenkes Jakarta III, 2018)
Based on previous research it was found that lemea (traditional food rejang) was proven to contain 2 types of lactic acid bacteria (BAL) namely L.aplantarum C410L1 and L. crossiae LS6 which could be probiotic and beneficial for health. The development of lemea as a potential probiotic must be proven its resistance to bile acids and salts as an indication of being able to survive in the gastrointestinal tract. This study aims to determine the resistance of BAL isolated from lemea against low pH, bile acids, and temperature. This research is an experimental study with all research units controlled. Analysis of BAL resistance to high temperatures, low pH, and bile salts was carried out in the Bengkulu Polytechnic Health Polytechnic laboratory. The total BAL colonies increased at 49 ° C and decreased at 64 ° C. The increase in the total number of BAL colonies within 0-30 hours occurred at pH 5 and pH 6. There was no increase or decrease in the total number of BAL colonies in salts 0.30%, 0.60%, and 0.90%. The diisolate lactic acid (BAL) bacteria from lemea have a temperature resistance of 42 ° C to 64 ° C, pH 2 to pH 7, have a salt resistance concentration of 0.30% to 0.90%. Lactic acid bacteria (BAL) which are diisolate from lemea have the potential as probiotics.